Transposition of a chromosomal segment bounded by redundant rRNA genes into other rRNA genes in Escherichia coli. - Hill, C W (1982)
We have constructed several mutants of Escherichia coli which have the chromosomal segment between the directly repeated rrnB and rrnE genes deleted from the normal position and transposed into another one of the seven redundant rRNA genes. We have examples where the transposition has been into rrnC, rrnD, rrnG, and rrnH. Included in the evidence for each of these transpositions was the finding that each transposition specifically affected a different one of the seven BamHI-PstI restriction nuclease fragments known to correspond to the seven rrn genes. The transposition mutants were generally healthy, but sensitive mixed-growth experiments revealed that most of them grew somewhat more slowly than the parental control in rich medium. The maximal detrimental effect was a 4 to 5% reduction in growth rate when the transposition of the rrnB-rrnE segment was into rrnG. We have found that a rrnF gene, reported by others to be linked to malA, does not exist in our standard strain, a derivative of Cavalli Hfr. Instead of rrnF, we identified a new rrn gene, rrnH, which mapped near min 5.